2012
DOI: 10.1103/physrevlett.109.173602
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of Coherent Feedback for Cooling Quantum Oscillators

Abstract: We model the cooling of open optical and optomechanical resonators via optical feedback in the linear quadratic Gaussian setting of stochastic control theory. We show that coherent feedback control schemes, in which the resonator is embedded in an interferometer to achieve all-optical feedback, can outperform the best possible linear quadratic Gaussian measurement-based schemes in the quantum regime of low steady-state excitation number. Such performance gains are attributed to the coherent controller's abilit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
176
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(178 citation statements)
references
References 39 publications
2
176
0
Order By: Relevance
“…Coherent feedback is a superset of measurement-based feedback [59], and it has been shown that coherent feedback can achieve better performance than measurement-based feedback in a number of settings, including noise reduction and cooling in linear systems [60,61], as well as noise reduction under bounded controls [59]. It has also been applied to generating nonlinear effects in mesoscopic systems [13,62].…”
Section: Example: Non-markovian Coherent Feedback Networkmentioning
confidence: 99%
“…Coherent feedback is a superset of measurement-based feedback [59], and it has been shown that coherent feedback can achieve better performance than measurement-based feedback in a number of settings, including noise reduction and cooling in linear systems [60,61], as well as noise reduction under bounded controls [59]. It has also been applied to generating nonlinear effects in mesoscopic systems [13,62].…”
Section: Example: Non-markovian Coherent Feedback Networkmentioning
confidence: 99%
“…The sideband fields are coherently fed back to the main interferometer. In some sense, this is one example of coherent feedback that has been extensively discussed in the quantum optics and control communities [8][9][10][11]. Depending on the choices of optical filters, different interferometer responses and sensitivities can be obtained.…”
Section: Introductionmentioning
confidence: 99%
“…We do not characterize performance in the quantum regime, but these devices feature regularly in such work and these capabilities are novel regardless. Moreover, because the network is linear and driven by Gaussian fields, the network characterization done in the classical regime should apply in the quantum one [1,[22][23][24][25][26][27]. Thus, we use the term ''coherent'' in the sense that an interferometer or resonator is coherent, which is the primary prerequisite for quantum dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…(Rigorous derivations are well covered in the literature, e.g., Refs. [1,[22][23][24][25]30,31].) Also, because it employs theoretical approaches developed by an electrical engineering community, familiar concepts in electromechanics are described in more detail than usual.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation